THE IMPACT OF SOCIAL MEDIA MARKETING AND STORE ATMOSPHERE ON CONSUMER SATISFACTION THROUGH PURCHASE DECISIONS AS INTERVENING VARIABLES AT LINGKIR COFFEE & IDEA TEMBALANG SEMARANG - Yogi Noviana, Putri; Anomsari, Ariati; Yovita, Lenni; Zakaria, Fakhmi (Universitas Islam Lamongan, 2025)
Competition in the Coffee shop industry forces entrepreneurs to be more aggressive in winning business competition. The purpose of this study is to determine the effect of social media marketing and store atmosphere on consumer satisfaction through purchasing decisions at Lingkar Coffee & Idea Tembalang Semarang. This study uses a quantitative approach with SEM PLS and SmartPLS 4 software. Samples were taken from Lingkar Coffee & idea customers. Data collection using a questionnaire with 100 respondents. The results of the study indicate that social media marketing and store atmosphere have a positive and significant effect on purchasing decisions, social media marketing and store atmosphere have a positive and significant effect on consumer satisfaction, purchasing decisions have a positive and significant effect on consumer satisfaction, purchasing decisions can mediate social media marketing and store atmosphere on consumer satisfaction.